Epidemiological and Clinical Characteristics of Sporadic Creutzfeldt–Jakob Disease: A Retrospective Study in Eastern China - Feng, Shuo; Zhao, Xinjing; Zhou, Xueying; Ye, Xiang; Yu, Xiaolin; Jiang, Wei; Deng, Yu; Zhou, Shengnian; Ma, Lin; Shan, Peiyan; Zhou, Guoyu (Frontiers in Neurology, 2021)
Objective: We aimed to characterize the epidemiological and clinical characteristics of sporadic Creutzfeldt–Jakob disease (sCJD) in eastern China in this retrospective study. Methods: This study enrolled 67 patients with sCJD hospitalized in a grade-A tertiary hospital in eastern China from January 2010 to January 2020. Demographic data, clinical symptoms, brain magnetic resonance imaging (MRI), electroencephalogram (EEG), cerebrospinal fluid (CSF) 14-3-3 protein test, polymerase chain reaction (PCR), and DNA sequence determination of genes were collected and analyzed. Results: There were 62 patients with probable sCJD and 5 patients with possible sCJD. Male (28 cases) to female (39 cases) ratio was 1:1.39. Mean age at disease onset was 64.42 ± 9.00 years (range: 29–88 years), and mean survival time was 9.39 ± 12.58 months (range: 1–60 months for patients who received the follow-ups). The most common onset symptoms were dementia (49.25%), movement disorder (44.78%), and visual disturbance (22.39%), while the most frequent clinical manifestations were language disorders (74.63%), ataxia (70.15%), and myoclonus (70.15%). The positive rates of brain MRI abnormalities, 14-3-3 protein in CSF, and periodic sharp wave complexes (PSWCs) on EEG were 84.90, 68.00, and 46.03%, respectively. The 14-3-3 protein positive (p = 0.033) and PSWCs on EEG (p = 0.020) acted as the favorable and unfavorable factor for over 1 year of survival time, respectively. Conclusions: There were some differences in epidemiological and clinical characteristics among patients in China and those of other countries. The prognosis and its influencing factors were relatively unexplored in China. The mean survival time of Chinese patients was longer than that of Caucasian patients but shorter than that of Japanese patients. The 14-3-3 protein in CSF and PSWCs on EEG were both closely related to the survival time. It is necessary to promote autopsy or biopsy to better understand sCJD in China.